1985
DOI: 10.1093/njaf/2.1.17
|View full text |Cite
|
Sign up to set email alerts
|

28-Year-Old Reproduction on Five Cutting Practices in Upland Oak1

Abstract: Knowledge of composition and development of stands following harvesting is prerequisite to forest management decisions. Conventional harvesting in mature upland oaks stands resulted in stands substantially different than the original. Twenty-eight-year-old reproduction following complete clearcutting, commercial clearcutting, diameter-limit cutting, selection cutting, and selection cutting with timber stand improvement indicated that the higher the residual overstory density the lower the frequency, diameter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The decline in oak and other more shade intolerant (sun loving) species is not unique to this study, other unmanaged forests (Christensen 1977, Nigh et al 1985, Barton and Schmelz 1987, Ward and Parker 1989, Ward and Stephens 1993 or forests that are partially harvested (Heiligmann et al 1985, Jokela and Sawtelle 1985, Smith and Miller 1987, Abrams and Scott 1989, Abrams and Nowacki 1992 1959-1970-1980-1990-Initial 1959-1970-1980-1970198019902000197019801990 Eastern tracts…”
Section: %mentioning
confidence: 74%
“…The decline in oak and other more shade intolerant (sun loving) species is not unique to this study, other unmanaged forests (Christensen 1977, Nigh et al 1985, Barton and Schmelz 1987, Ward and Parker 1989, Ward and Stephens 1993 or forests that are partially harvested (Heiligmann et al 1985, Jokela and Sawtelle 1985, Smith and Miller 1987, Abrams and Scott 1989, Abrams and Nowacki 1992 1959-1970-1980-1990-Initial 1959-1970-1980-1970198019902000197019801990 Eastern tracts…”
Section: %mentioning
confidence: 74%
“…Similarly, the proportion of oak reproduction was low (10% of all dominant and codominant stems) in 5-17-yearold stands that had originated after clearcutting oak-dominated forests in southern Indiana (Fischer 1987), but the relative density of dominant oak increased over time in those same stands predominantly on the drier, more xeric and less productive stands (Morrissey et al 2008). Heiligmann et al (1985) reported that the proportion of oak in the reproduction following clearcutting ranged from 13% on north slopes to 54% on south slopes 28 years after harvesting oak forests in southeastern Ohio. They concluded that red maple had reduced oak stocking from levels in the original stand on north slopes (site index 66 ft black oak) and that stands on south slopes (site index 63 ft black oak) would remain predominantly oak-hickory in composition.…”
Section: Restricted Trafficmentioning
confidence: 99%